2004
DOI: 10.1542/peds.2003-0763-l
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Emotional Adjustment of Teenagers in Mainstream School Who Were Born Before 29 Weeks’ Gestation

Abstract: Compared with mainstream classmates, children who are born extremely early continue to have higher levels of parent- and teacher-reported emotional, attentional, and peer problems well into their teens. However, despite these problems, they do not show signs of more serious conduct disorders, delinquency, drug use, or depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
68
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 42 publications
10
68
1
3
Order By: Relevance
“…In particular, the use of self-report versus informant ratings can produce widely different outcomes. [16,17] The majority of studies have used behavioural screening questionnaires as these are cost and time efficient for large-scale investigations. Two have emerged as the most popular assessment tools facilitating international and cross-cultural comparisons: the Achenbach System of Empirically Based Assessment (ASEBA) [18], comprising the Child Behavior Checklist (CBCL), Teacher's Report Form (TRF) and Youth Self-Report (YSR), and the Strengths and Difficulties Questionnaire (SDQ) [19] comprising parent, teacher and self-report scales.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the use of self-report versus informant ratings can produce widely different outcomes. [16,17] The majority of studies have used behavioural screening questionnaires as these are cost and time efficient for large-scale investigations. Two have emerged as the most popular assessment tools facilitating international and cross-cultural comparisons: the Achenbach System of Empirically Based Assessment (ASEBA) [18], comprising the Child Behavior Checklist (CBCL), Teacher's Report Form (TRF) and Youth Self-Report (YSR), and the Strengths and Difficulties Questionnaire (SDQ) [19] comprising parent, teacher and self-report scales.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…However, there are notable exceptions in some studies in which no significant differences were found. [27,76] Furthermore, where teenagers self-reported, some found higher anxious/depressed or emotional scores [17,77] while others did not find any differences compared to full term controls. [16,24] Thus emotional problems are more likely to be rated by parents or teachers than by the teenagers themselves.…”
Section: Emotional Disordersmentioning
confidence: 96%
See 1 more Smart Citation
“…The social development of children born extremely preterm is problematic (Gardner, Johnson, Yudkin, & al., 2004;Msall & Park, 2008). Problems in affective and behavioural regulation as well as impoverished social skills are common.…”
mentioning
confidence: 99%
“…There has also been an increased awareness of the vulnerability of adolescent and adult survivors of very and extremely preterm birth to increased rates of behavior and mental health disorders (Gardner et al 2004). This is highlighted in Table 4.…”
Section: Behavioral/emotional Disordersmentioning
confidence: 99%